Technological appropriation by mapuche communicators. Reflections from communicative practices - Maldonado Rivera, Claudio Andrés (2019)
This paper analyzes the practices of "technological appropriation" carried out by mapuche communicators, in the context of the chilean-mapuche intercultural and interethnic conflict. The results presented were obtained through an Argument Analysis applied to a set of interviews with mapuche communicators from La Araucanía region, Chile. The central-arguments identified dialogue with theoretical categories, to develop a dialogue of knowledge between the experiential and the theories of the social and human sciences. The work concludes that the practices of technological appropriation are related to issues such as identity, vindication, communication and interculturality, in addition to recognizing their implications in the strengthening of the political and identity project of reconstruction of the Mapuche country.